Mouse embryonic stem cells - Evans, Martin (Henry Stewart Talks, 2007)
Where Embryonic stem cells come from, Testicular teratocarcinomas, Differentiation of EC cells, Interrelationships, Isolation of embryonic stem cells, Experimental mammalian genetics, ES cells are a vector to the whole animal genome, Mutation introduced via ES cells, Consideration of the present situation